PROFIL IMPLEMENTASI PROGRAM KESELAMATAN DAN KESEHATAN KERJA (K3) PADA KARYAWAN DI RUANG PACKING PT NARMADA AWET MUDA - Maulana, Alfi; Aini, Aini (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2024)
The study aims to analyze Health, Accident, and Safety (K3) in employees at PT Narmada Awet Muda. The study uses quantitative descriptive methods. The purpose of this study is to conduct, inspect, investigate and evaluate risks at potentially hazardous places in the packing room of PT Narmada Muda. The sample used in this study was the entire worker on the packing part. Conclusions Implementation of the occupational health and safety program in the packing room of PT Narmada Awet Muda showed good results based on inspection investigation and risk assessment to prevent the occurrence of danger